BUDIDAYA DAN KEUNTUNGAN PETANI PADI (Oryza sativa L) DI DESA KIRAM KECAMATAN KARANG INTAN KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - Bahrun Bahrun (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2016)
To the effect of observational it to know technically paddy farming management and to know eknomis's ala hits cost, acceptance and paddy farming gain varietas Pandak at Silvan Kiram. This research utilize survey method with tech observation, panarikan samples to utilize simple random tech( Simple random is sampling) ,  Total varietas Pandak's paddy farmer at Silvan Kiram as much 102 person. Take at random simple( Simple Random is Sampling ) as much 20 % (20 person) of all population.  Acquired production average as big as 3.497,40 kg / farmers. Accepting acquired acceptance paddy farmer average as big as Rp. 27. 979. 200,00 / Average gain which gotten by farmer as big as Rp. 15. 338. 796,62 / farmers